Digital media preferences’ transformation of modern Russian youth in connection with new realities - D. V. Dolgopolov; A. I. Eremeeva (Цифровая социология, 2023)
The article considers features of modern Russian youth media preferences transformation against the activity’s restrictions of digital social platforms as Instagram, TikTok, etc. The authors have assumed that the “flow” of youth audience to other platforms would occur at a very rapid pace, and new platforms would be mastered in the shortest possible time, i.e. adaptation would be maximally effective. It has also been hypothesized that new platforms creation would attract youth audience, which would seek to “close” their consumer preferences through the newly emerging digital platforms in Russia, replacing those that were legally restricted. To test the above hypotheses, we have surveyed young people aged 18–24, who are the main audience that, according to the hypothesis of this study, would be most affected by media environment transformation. The main hypotheses have been tested by means of several blocks of questions to which the respondents gave answers first within the framework of a standardized questionnaire and then in free form within the framework of interviewing by the researchers. As a result of the study, it has been found out that the specifics of media preferences transformation among young people is not so significant compared to general changes in society, and therefore recommendations for further research directions have been put forward.